A case of surgical site infection in a recipient after transplantation of the kidney infected with Klebsiella pneumoniae - N. V. Shmarina; A. Rustambek Uulu; I. V. Dmitriev; A. G. Balkarov; R. V. Storozhev; N. S. Zhuravel; D. V. Lonshakov; K. E. Lazareva (Трансплантология (Москва))
Background. A surgical site infection caused by bacterial flora of a bacteria-contaminated kidney graft is an exceedingly rare occurrence and is poorly described in the literature. However, such cases entail the risk of resulting in a graft loss and recipient death, and therefore should be attended to by a specialized team of experts.Objective. This Case Report presents a rare instance of a surgical site infection in a kidney recipient following the transplantation of an unintentionally Klebsiella pneumoniae-infected graft.Material and methods. The clinical case was a 49-year-old male suffering from stage 5 chronic kidney disease who underwent a kidney transplantation from a cadaveric asystolic donor. The clinical case was described using the results of laboratory tests, instrumental and pathomorphologic investigations obtained from the recipient medical history and observation chart, and the organ donor's passport.Results. This Case Report has described a clinical presentation of the surgical site infection with K. pneumoniae bacteria in a recipient of the infected kidney graft, and the treatment outcome.Conclusions. In the event of infection developing in a bacteria-contaminated kidney graft, it is imperative to be suspicious of a deep infection. In the event of progressively developing abscesses, phlegmon in the graft bed and other related localizations, or the course of infection by the type of necrotizing cellulitis/fasciitis with no effect from antibacterial therapy, it is imperative to perform urgent surgical intervention with a wide opening of the foci and removal of the kidney graft as a source of the infectious process. This should be combined with an adequate antibacterial therapy and the withdrawal of immunosuppression.